Meta-clay geopolymer as encapsulator of FBG temperature sensor. (2018) - Ahmadi, H.; Muntini, M.S.; Subaer,
Abstract: A study about design of temperature sensor system based on Fiber Bragg Grating (FBG) with encapsulation method has been conducted. Encapsulation of FBG used meta-clay geopolymer ceramic-tube. The results of the measurement showed that the coefficient of thermal expansion of the material was (α)-54.91 × 10 −6 K −1 . Chemical composition, crystallinity as well as surface morphology of ceramic-geopolymers were examined by using Scanning Electron Microscopy (SEM) and X-Ray Diffraction (XRD). FBG sensor measurement performed at temperature from 50 °C to 250 °C. Characteristics of the FBG temperature sensor that used encapsulation method is obtained sensitivity 11 pm °C −1, linearity of 99, 31% and good repeatability.